PROFIL PENDERITA HIPERTENSI DI RSUD PASAMAN BARAT TAHUN 2022 - Abdullah, Dessy; Nadia Purnama Dewi; Divna Monaprlya; Zamsari Chan (Yayasan Nusantara Hasana Berdikari, 2024)
The prevalence of hypertension is increasing worldwide, especially in developing countries. The process by which hypertension occurs cannot be known clinically, so hypertension is often referred to as the silent killer because this disease does not show early clinical symptoms. This study aims to determine the profile of hypertension sufferers at West Pasaman Regional Hospital. This research covers the scope of Internal Medicine and Public Health Sciences. The research location is West Pasaman Regional Hospital. The research period is September 2022 to February 2023. The type of research is descriptive. The research design was cross sectional design. The population reached by outpatient hypertensive patients with a total population of 479 patients registered in the West Pasaman Regional Hospital's medical records in 2022 is 90 samples using a purposive sampling technique. Univariate data analysis is presented in the form of a frequency distribution and data processing uses the computerized SPSS program IBM version 25.0. The largest age group is pre-advanced (45-59 years), namely 42 people (46.7%), the largest gender is female, namely 48 people (53.3%), the highest status is working, namely 50 people (55.6%), The highest systolic blood pressure was grade I, namely 52 people (57.8%), the highest diastolic blood pressure was grade I, namely 60 people (66.7%), there was a relationship between age and blood pressure in hypertension sufferers at West Pasaman District Hospital. (p=0.000), there is a relationship between gender and blood pressure in hypertension sufferers at West Pasaman Regional Hospital. (p=0.021) and there is a relationship between work and blood pressure in hypertension sufferers at West Pasaman Regional Hospital. (p=0.008). It has been proven that there is a relationship between age and blood pressure in hypertension sufferers, there is a relationship between gender and blood pressure and there is a relationship between work and blood pressure in hypertension sufferers at the West Pasaman District Hospital.